2009
DOI: 10.1186/1475-2840-8-35
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of a Paleolithic diet on cardiovascular risk factors in type 2 diabetes: a randomized cross-over pilot study

Abstract: Background: Our aim was to compare the effects of a Paleolithic ('Old Stone Age') diet and a diabetes diet as generally recommended on risk factors for cardiovascular disease in patients with type 2 diabetes not treated with insulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
316
4
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(344 citation statements)
references
References 65 publications
(69 reference statements)
15
316
4
9
Order By: Relevance
“…She did not consume offal on a regular basis. This version of the paleolithic diet conforms neither to the paleolithic diet as originally described by Cordain [11] or Lindeberg [14] nor any of those versions in previously published clinical studies of the paleolithic diet [15,16,17,18]. We therefore refer to this diet as a 'popular paleolithic diet' because it appears to arise from a mixture of scientific and unscientific information, much of which is probably gleaned from dubious sources on the internet.…”
Section: The Popular Paleolithic Dietmentioning
confidence: 99%
“…She did not consume offal on a regular basis. This version of the paleolithic diet conforms neither to the paleolithic diet as originally described by Cordain [11] or Lindeberg [14] nor any of those versions in previously published clinical studies of the paleolithic diet [15,16,17,18]. We therefore refer to this diet as a 'popular paleolithic diet' because it appears to arise from a mixture of scientific and unscientific information, much of which is probably gleaned from dubious sources on the internet.…”
Section: The Popular Paleolithic Dietmentioning
confidence: 99%
“…In obese individuals [149] and healthy subjects who underwent eccentric exercise training [150], the inflammatory state was further augmented postprandially through a high CHO intake, but not through high-fat, low CHO meals in the latter study. Maybe more importantly, even moderate CHO restriction has been shown to effectively target several important markers of atherosclerosis and type II diabetes, both of which are associated with chronic inflammation [151][152][153][154][155][156][157]. Forsythe et al showed that in overweight individuals with dyslipidemia a very low CHO diet had a more favorable effect than a low fat diet in reducing several markers of inflammation [158].…”
Section: Avoidance Of Chronic Inflammationmentioning
confidence: 99%
“…Similarly, in a clinical trial on normal healthy sedentary subjects that consumed a Paleolithic diet (lean meat, fruit, vegetables and nuts) for 10 days, there was an observable improvement in blood pressure, a decrease in insulin secretion, an increase in insulin sensitivity, and an improvement in blood lipid profiles [3]. Equally, in a randomized cross-over study of three months duration, diabetic patients receiving a Paleolithic diet (lean meat, fish, fruit, vegetables, root vegetables, eggs, and nuts) showed a reduction in body weight, BMI and waist circumference, lower HbA1c, TAG and diastolic blood pressure, and an improvement in glycaemic control [12]. These studies are further supported by Lindeberg et al [13] who reported that patients with ischemic heart disease concomitant with glucose intolerance or type 2 diabetes had a large improvement in insulin sensitivity and glucose tolerance when receiving a Paleolithic diet.…”
Section: Insulin Resistance and Our "Primitive" Genomementioning
confidence: 99%